Saline water intrusion toward groundwater: issues and its control - Purnama, Setyawan; Marfai, Muh Aris (JNRD - Journal of Natural Resources and Development, 2012)
Nowadays, saline water pollution has been gaining its importance as the major issue around the world, especially in the urban coastal area. Saline water pollution has major impact on human life and livelihood. It´s mainly a result from static fossil water and the dynamics of sea water intrusion.. The problem of saline water pollution caused by seawater intrusion has been increasing since the beginning of urban population. The problem of sea water intrusion in the urban coastal area must be anticipated as soon as possible especially in the urban areas developed in coastal zones,. This review article aims to; (i) analyze the distribution of saline water pollution on urban coastal area in Indonesia and (ii) analyze some methods in controlling saline water pollution, especially due to seawater intrusion in urban coastal area. The strength and weakness of each method have been compared, including (a) applying different pumping patterns, (b) artificial recharge, (c) extraction barrier, (d) injection barrier and (e) subsurface barrier. The best method has been selected considering its possible development in coastal areas of developing countries. The review is based considering the location of Semarang coastal area, Indonesia. The results have shown that artificial recharge and extraction barrier are the most suitable methods to be applied in the area.
Keywords: Groundwater; Saline water pollution; Seawater intrusion control